Management of a Female Patient with Irritable Bowel Syndrome and Somatoform Disorder - E. A. Trush; E. A. Poluektova; A. G. Beniashvili; O. S. Shifrin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim: to demonstrate the management of a patient with somatization disorder and irritable bowel syndrome.Key points. A 41-yo female patient was admitted with complains of spastic lower abdomen pain, hard stool once every 1–2 days under laxative treatment (macrogol), bloating, anxiety, waiting for confirmation of a life threatening illness, internal stress, difficulty in falling asleep, shallow sleep. Has a long history of disease, characterized by the appearance of a variety of somatic symptoms (headache, tachycardia, joint pain, stool disorders, abdominal pain, etc.) during periods of emotional tension, lack of data suggesting organic disease. No abnormal changes were detected in examination at the clinic (complete blood count, serum chemistry tests, urinalysis or fecal tests, hydrogen and methane breath tests with lactulose, abdominal ultrasound, esophagogastroduodenoscopy, colonoscopy). With the prior agreement of patient, she was consulted by a psychiatrist and diagnosed with somatization disorder and mild anxiety disorder. On discharge from hospital recommended cognitive-behavioral therapy, continue taking macrogol, as well as treatment with Kolofort. After 3 months of complex treatment, there was a significant decrease in the severity of both the symptoms of irritable bowel syndrome and anxiety disorder.Conclusion. For patients whose complaints meet the diagnostic criteria for IBS, a two-stage differential diagnosis may be justified: at the first stage, differentiation of IBS and organic diseases of the gastrointestinal tract is carried out; at the second stage - IBS and somatization disorder. Kolofort can be the drug of choice both in patients with IBS and the pharmacological part of therapy in patients with somatization disorder.